Post-COVID Recovery Assessment Clinics: A Real Need of Time - Muhammad Ahmer Raza; Shireen Aziz; Sana Shahzad; Shahid Masood Raza (University of Minnesota Libraries Publishing, 2021)
COVID-19 is an infectious respiratory and vascular disease caused by SARS-CoV-2. This virus was first identified in Wuhan, China and caused an ongoing pandemic. The World Health Organization (WHO) declared the outbreak a public health emergency of international concern in January 2020 and a pandemic in March 2020. Reports suggest that patients experience persistent deficits in pulmonary and cognitive functioning, as well as multifaceted health issues and worsened quality of life. From records in Italy and France, COVID-19 survivors experience the return of symptoms. COVID-19 survivors need specialist investigation once they have been discharged from hospital. No proper guidelines are recommending that COVID-19 survivors should be under assessment. We intended to provide a model to assist local healthcare systems to establish post-COVID recovery assessment clinic(s) for CVOID-19 survivors. Our model will enable COVID-19 patients' access to multi-professional advice, so that they are put onto the right clinical pathway to treat their symptoms. Furthermore, the findings of different specialties in post-COVID recovery assessment clinic(s) may help doctors determine the best discharge plan for COVID-19 patients.